Comparing L1 With L2 Acquisition: How Learning Factors and Stages Reveal Differences and Similarities Between the Two Processes - Viáfara, John Jairo (Universidad Pedagógica y Tecnológica de Colombia, 2013)
AbstractThis article reviews some of the literature and research studies which explore first and second language acquisition in order to make a parallel between these two processes. The discussion takes into consideration cognitive, affective and socio-cultural factors which influence the learning of L1 and L2. In addition, a comparison of L1 and L2 language acquisition sequences helps to inform about the similarities and differences. Key Words: First and second language acquisition, Language learning factors, Sequence of acquisition, Language acquisition theorieS.